Pelvic floor symptoms, physical, and psychological outcomes of patients following surgery for colorectal cancer. (3rd June 2018) - Lin, Kuan-Yin; Denehy, Linda; Frawley, Helena C.; Wilson, Lisa; Granger, Catherine L.
ABSTRACT: Background: Little has been published regarding general and pelvic floor-related health status in patients who have undergone surgery for colorectal cancer (CRC). Objective: The objective of the study was to assess changes in pelvic floor symptoms, physical activity levels, psychological status, and health-related quality of life (HRQoL) in patients with CRC from pre- to 6 months postoperatively. Methods: Pelvic floor symptoms, physical activity levels, anxiety and depression, and HRQoL of 30 participants who were undergoing surgery for stages I–III CRC were evaluated pre- and 6 months postoperatively. Results: Six months postoperatively, there were no significant changes in severity of pelvic floor symptoms, or other secondary outcomes (physical activity levels, depression, global HRQoL) compared to preoperative levels ( p > 0.05). However, fecal incontinence ( p = 0.03) and hair loss ( p = 0.003) measured with the HRQoL instrument were significantly worse. Participants were engaged in low levels of physical activity before (42.3%) and after surgery (47.4%). Conclusion: The findings of a high percentage of participants with persistent low physical activity levels and worse bowel symptoms after CRC surgery compared to preoperative levels suggest the need for health-care professionals to provide information about the benefits of physical activity and bowel management at postoperative follow-ups. Further investigation in larger studies is warranted.